Nutrient enrichment in a temperate macro-tidal system : scenario analysis and contribution to coastal management - Neto, João Miguel Magalhães (2004)
Tese de doutoramento em Biologia (Ecologia)apresentada à Fac. de Ciências e Tecnologia da Univ. de Coimbra